2014
DOI: 10.1155/2014/564679
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Its Associated Risk Factors in the Kingdom of Saudi Arabia, 2013: A National Survey

Abstract: Current data on hypertension in the Kingdom of Saudi Arabia are lacking. We conducted a national survey to inform decision-makers on the current magnitude of the epidemic. We measured systolic and diastolic blood pressure of 10,735 Saudis aged 15 years or older and interviewed them through a national multistage survey. We used multivariate logistic regressions to describe sociodemographic characteristics and risk factors of hypertensive, borderline hypertensive, and undiagnosed hypertensive Saudis. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
190
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(221 citation statements)
references
References 14 publications
21
190
9
1
Order By: Relevance
“…Previous study in 2005 showed that 25.5% has hypertension and only 44.7% of them were aware of the disease. 8 Many studies have shown that overweight individuals have two to six times the risk of being hypertensive. 2 Furthermore, overweight individuals have five times the risk of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study in 2005 showed that 25.5% has hypertension and only 44.7% of them were aware of the disease. 8 Many studies have shown that overweight individuals have two to six times the risk of being hypertensive. 2 Furthermore, overweight individuals have five times the risk of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…While it has commonly been reported that the causes of HTN are not known, this is only partially correct as the scientists have inadequate evidence about genetic variations or genes that are under-expressed or over-expressed and may cause high BP (11) . On the other hand, the literature illustrated several risk factors that may increase BP and lead to HTN.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is a significant worldwide health problem, including the Kingdom of Saudi Arabia (KSA) (1)(2)(3)(4)(5). These problems are associated with both systolic blood pressure (SBP) and diastolic blood pressure (DBP) levels (6).…”
mentioning
confidence: 99%